2018
DOI: 10.7326/m17-2701
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Nine Risk Prediction Models for Selecting Ever-Smokers for Computed Tomography Lung Cancer Screening

Abstract: Intramural Research Program of the National Institutes of Health/National Cancer Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(151 citation statements)
references
References 35 publications
0
148
1
2
Order By: Relevance
“…We also applied the Cτ index to ever smokers at risk of lung cancer incidence and subsequent death. The four best performing lung cancer models (identified as such in the previously published work) had previously reported differences in calibration performance in ethic/racial subgroups . We examined discrimination ability in ethic/racial subgroups of the NLST; despite using information from both lung cancer incidence and death, the Cτ index was not able to find a statistically significant difference in discrimination ability.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also applied the Cτ index to ever smokers at risk of lung cancer incidence and subsequent death. The four best performing lung cancer models (identified as such in the previously published work) had previously reported differences in calibration performance in ethic/racial subgroups . We examined discrimination ability in ethic/racial subgroups of the NLST; despite using information from both lung cancer incidence and death, the Cτ index was not able to find a statistically significant difference in discrimination ability.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis found that these models performed less well in racial/ethnic minorities likely because the data sets used to develop the models were predominantly caucasian . The differences in calibration ability of these models in racial/ethnic minorities have previously been described; we used the Cτ index to examine potential differences in discrimination ability of these models in racial/ethnic minorities.…”
Section: Applications Of the C∗ Indexmentioning
confidence: 97%
See 3 more Smart Citations